LiBAlF6:Cr3+ (B = Ca, Sr) fluoride phosphors with ultra-broad near-infrared emission for NIR pc-LEDs. Issue 1 (1st January 2022) - Wu, Di; Liu, Lili; Liang, Heng; Duan, Huangbin; Nie, Wendong; Wang, Junrong; Peng, Jiaqing; Ye, Xinyu
Abstract: Compared with oxide-based NIR phosphors, fluoride phosphors have received great attention recently due to their good thermal resistance and high photoelectric efficiency. In this work, novel LiBAlF6 :Cr 3+ (B = Ca, Sr) with low phonon energy and relatively weak electron-phonon coupling were synthesized through a facile hydrothermal approach. Benefiting from low Dq/B, an ultra-broad NIR emission extending from 650 nm to 1100 nm can be achieved in these phosphors under excitation of blue light. Among them, LiSrAlF6 :Cr 3+ presents a FWHM of 155 nm. At 423 K, LiCaAl0.4 F6 : 0.6Cr 3+ and LiSrAl0.4 F6 : 0.6Cr 3+ maintain 66.63% and 55.47% of their initial intensities, respectively. Better thermal stability of LiCaAlF6 : Cr 3+ could be attributed to the broad band gap and weak electron-phonon coupling effect. Photoelectric conversion efficiencies of 5.002% and 5.468% at 300 mA could be obtained for NIR pc-LEDs packaged with LiCaAl0.4 F6 : 0.6Cr 3+ and LiSrAl0.4 F6 : 0.6Cr 3+, respectively. A slightly internal bruise inside apple and water level behind trademark in bottle could be clearly detected, revealing that LiBAlF6 :Cr 3+ (B = Ca, Sr) phosphors have great application potential in infrared inspection.